MOBILITY AND DISCOURSE CIRCULATION IN THE CONTEMPORARY WORLD: THE TURN OF THE REFERENTIAL SCREW - Fabrício, Branca Falabella (Revista da Anpoll, 2016)
In this paper I call into question the referential paradigm, drawing on the conceptual framework developed by contemporary Anthropology, Linguistic Anthropology, Sociolinguistics and Applied Linguistics. I call for the urgent problematization of the so-called referential metaphysics while arguing that constructs such as entextualization and indexicality can shake the strong representational tradition in the field of language studies – a tradition sustained by an infectious modernist linguistic ideology and authoritarian and monist models of reality. The latter have been losing ground, as an explanatory apparatus, amidst the intense mobility and complexity of globalization processes which require new theoretical-analytical tools. This work is licensed under a Creative Commons Attribution 3.0 License.